Synthesis of cell composite alginate microfibers by microfluidics with the application potential of small diameter vascular grafts. (7th June 2017) - Liu, Mingying; Zhou, Zhizhi; Chai, Yongchao; Zhang, Shuai; Wu, Xiaomeng; Huang, Shaopeng; Su, Jiaqiang; Jiang, Jiahuan
Abstract: Fabrication of small diameter vascular grafts (SDVGs) with appropriate responses for clinical application is still challenging. In the present work, the production and characterization of solid alginate based microfibers as potential SDVG candidates through the method of microfluidics were considered original. A simple glass microfluidic device with a 'L-shape' cylindrical-flow channel in the microfluidic platform was developed. The gelation of microfibers occurred when the alginate solution and a CaCl2 solution were introduced as a core flow and as a sheath flow, respectively. The diameters of the microfibers could be controlled by varying the flow rates and the glass capillary tubes diameters at their tips. The generated microfibers had somewhat rough and porous surfaces, their suture retention strengths were comparable to the strength of other tissue engineered grafts. The encapsulated mesenchymal stem cells proliferated well in the microfibers, and showed a stable endothelialization under the angiogenesis effects of vascular endothelial growth factor and fibroblastic growth factor. The in vivo implant into the mice abdomens indicated that cell composite microfibers caused a mild host reaction. These encouraging results suggest great promise of the application of microfluidics as a future alternative in SDVGs engineering.